Ecological Biogeography of the Terrestrial Nematodes of Victoria Land, Antarctica - Byron Adams; Diana Wall; Ross Virginia; Emma Broos; Matthew Knox (ZooKeys, 2014)
The terrestrial ecosystems of Victoria Land, Antarctica are characteristically simple in terms of biological diversity and ecological functioning. Nematodes are the most commonly encountered and abundant metazoans of Victoria Land soils, yet little is known of their diversity and distribution. Herein we present a summary of the geographic distribution, habitats and ecology of the terrestrial nematodes of Victoria Land from published and unpublished sources. All Victoria Land nematodes are endemic to Antarctica, and many are common and widely distributed at landscape scales. However, at smaller spatial scales, populations can have patchy distributions, with the presence or absence of each species strongly influenced by specific habitat requirements. As the frequency of nematode introductions to Antarctica increases, and soil habitats are altered in response to climate change, our current understanding of the environmental parameters associated with the biogeography of Antarctic nematofauna will be crucial to monitoring and possibly mitigating changes to these unique soil ecosystems.